The influence of preschool children's diets on the risk of lifestyle diseases. A pilot study - Małgorzata Kostecka (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. A healthy diet in early life not only contributes to physical and intellectual development, but it can also reduce the risk of disease in adulthood. There is growing evidence to indicate that childhood diets are highly correlated with health in adult years. Eating habits formed in childhood persist in later life. Objective. The objective of this study was to evaluate the diets of preschool children aged 3 to 6 years and to identify statistical correlations between dietary factors and the risk of lifestyle diseases. Material and methods. The described survey was conducted based on the paper and pencil interviewing method. The study was conducted on 380 children from Lublin and Świętokrzyskie regions. The risk of lifestyle diseases in the studied population was evaluated based on the answers to 17 selected questions. The questionnaires were processed statistically in SPSS and Statistica programs. Results. Eating irregular meals increased the risk of lifestyle diseases, and the lower the number of meals per day, the greater the relevant risk (p=0.002). Children who did not eat regular breakfasts or afternoon teas and ate sweet and salty snacks were at significantly higher risk of lifestyle diseases. Consumption of milk and dairy product was an important predictor of lifestyle diseases. Children who did not drink milk every day were at significantly higher risk of developing lifestyle diseases than their peers who drank milk at least once a day (pConclusions. Eating habits formed in childhood can contribute to the risk of lifestyle diseases in adulthood. Particularly dangerous are nutritional habits leading to overweight and obesity. Both children and parents require nutritional education to develop healthy eating habits.